198TiPSPOTLIGHT: Comparison of zolbetuximab or placebo + mFOLFOX6 as first-line treatment in patients with claudin18.2+/HER2– locally advanced unresectable or metastatic gastric or gastroesophageal junction adenocarcinoma (GEJ): A randomized phase III study. (24th November 2019) - Yamaguchi, K; Shitara, K; Al-Batran, S-E; Bang, Y-J; Catenacci, D; Enzinger, P; Ilson, D; Kim, S; Lordick, F; Shah, M; Van Cutsem, E; Xu, R-H; et al.
Abstract: Background: Gastric cancer (GC) is the fourth leading cause of cancer death worldwide, with disproportionate incidence and mortality rates reported for people from Eastern Asia. Fluorouracil (5-FU), folinic acid, and oxaliplatin (mFOLFOX6) is an accepted chemotherapy for first-line treatment of locally advanced/metastatic GC/GEJ. Recently, Claudin (CLDN)18.2 has emerged as a promising targetable biomarker. In healthy tissue, CLDN18.2 is confined to gastric mucosa tight junctions. Upon malignant transformation, cell polarity perturbations lead to exposure of CLDN18.2 on the cell surface. Zolbetuximab is a chimeric IgG1 monoclonal antibody that specifically binds to CLDN18.2 and mediates cell death through antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. In a randomized phase 2 study (NCT01630083), patients with CLDN18.2 + advanced GC/GEJ treated with zolbetuximab + epirubicin, oxaliplatin, and capecitabine (EOX) showed prolonged survival compared with EOX alone. Trial design: This phase 3, double-blind, placebo-controlled study (NCT03504397) will enroll ∼550 adult patients from global sites, Japan, Republic of Korea, and Taiwan. Patients with CLDN18.2 + /HER2 – locally advanced unresectable or metastatic GC or GEJ who have not been previously treated with chemotherapy will be eligible. Patients will be randomized 1:1 to receive zolbetuximab + mFOLFOX6 or placebo + mFOLFOX6. Zolbetuximab will be administered by IV infusion as an 800-mg/m 2 loading dose followed by 600 mg/m 2 Q3W and mFOLFOX6 Q2W. During screening, central testing of tumor tissue will determine CLDN18.2 and HER2 status (if unknown); patients will be considered CLDN18.2 + if ≥ 75% of tumor cells demonstrate moderate-to-strong IHC staining. The primary objective is to compare the progression-free survival between treatment arms. The key secondary efficacy endpoint is overall survival. Objective response rate, duration of response, safety/tolerability, PK, and immunogenicity of zolbetuximab are other secondary endpoints. Clinical trial identification: NCT03504397. Legal entity responsible for the study: Astellas Pharma US, Inc. Funding: Astellas Pharma US, Inc. Disclosure: K. Yamaguchi: Research grant/Funding (self): Astellas Pharma, Inc.; Research grant/Funding (self): Eli Lilly; Research grant/Funding (self): Taiho Pharmaceutical; Research grant/Funding (self): Chugai Pharmaceutical; Research grant/Funding (self): Merck Serono; Research grant/Funding (self): Takeda; Research grant/Funding (self): Daiichi-Sankyo; Research grant/Funding (self): Ono Pharmaceutical; Research grant/Funding (self): Bristol-Myers Squibb; Research grant/Funding (self): Bayer; Research grant/Funding (self): Yakurt Honsha; Research grant/Funding (self): Dainippon Sumitomo; Research grant/Funding (self): Boehringer Ingelheim; Research grant/Funding (self): Gilead. K. Shitara: Advisory / Consultancy, Research grant / Funding (institution): Astellas Pharma; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Takeda; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self): Novartis; Honoraria (self): AbbVie; Honoraria (self): Yakult; Research grant / Funding (institution): Dainippon Sumitomo Pharma; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Taiho Pharmaceutical; Research grant / Funding (institution): Chugai Pharma; Advisory / Consultancy, Research grant / Funding (institution): MSD; Research grant / Funding (institution): Medi Science. S-E. Al-Batran: Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Celgene; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Lilly; Advisory / Consultancy: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy: SERVIER; Speaker Bureau / Expert testimony: Nordic Bioscience; Research grant / Funding (institution): Hospira; Research grant / Funding (institution): Medac; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Roche Pharma AG; Research grant / Funding (institution): Vifor Pharma. Y-J. Bang: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy, Research grant / Funding (institution): Merck Serano; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly; Advisory / Consultancy, Research grant / Funding (institution): Taiho; Advisory / Consultancy, Research grant / Funding (institution): Daiich-Sankyo; Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy, Research grant / Funding (institution): BeiGene; Advisory / Consultancy, Research grant / Funding (institution): GreenCross; Advisory / Consultancy, Research grant / Funding (institution): Samyang Biopharm; Advisory / Consultancy: Hanmi; Advisory / Consultancy, Research grant / Funding (institution): Genexine; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): MacroGenics. D. Catenacci: Honoraria (self): Astellas; Honoraria (self): Merck; Honoraria (self): BMS; Honoraria (self): Lilly; Honoraria (self): Gristone; Honoraria (self): Taiho; Honoraria (self): Genetech/Roche; Honoraria (self): Daichii Sankyo . P. Enzinger: Advisory / Consultancy: Merck; Advisory / Consultancy: Astellas; Advisory / Consultancy: Celgene; Advisory / Consultancy: Lilly; Advisory / Consultancy: Loxo; Advisory / Consultancy: Taiho. D. Ilson: Honoraria (self), Advisory / Consultancy: Astellas. S. Kim: Advisory / Consultancy: Astellas. F. Lordick: Advisory / Consultancy: Astellas; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: BMS; Advisory / Consultancy: AstraZeneca. E. Van Cutsem: Advisory / Consultancy: Astellas; Advisory / Consultancy: AstraZeneca; Research grant / Funding (institution): Amgen; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): Celgene; Research grant / Funding (institution): Ipsen; Advisory / Consultancy: Incyte; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy, Research grant / Funding (institution): Merck KGaA; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Servier . A. Arozullah: Full / Part-time employment: Astellas. J. Wook Park: Full / Part-time employment: Astellas Pharma Global Development Inc. J. Ajani: Advisory / Consultancy, Research grant / Funding (institution): Astellas. All other authors have declared no conflicts of interest.